2021
DOI: 10.1108/jmtm-10-2020-0382
|View full text |Cite
|
Sign up to set email alerts
|

A digital readiness check for the evaluation of supply chain aspects and company size for Industry 4.0

Abstract: PurposeWhile there are several readiness assessments regarding digital transformation (DT) and Industry 4.0 in extant literature, this study aims to contribute to (a) a better understanding of digital readiness in supply chain (SC) aspects and (b) elaborate on differences between small and medium-sized enterprises (SMEs) and large enterprises.Design/methodology/approachThe study is based on 409 companies that participated in the Digital Readiness Check (DRC) in the region of Salzburg (Austria) and Bavaria (Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 36 publications
1
50
1
2
Order By: Relevance
“…Furthermore, studies have predominantly quantified Industry 4.0 development by measuring aspects such as strategy, organizational culture and technology (Kırmızı and Kocaoglu, 2022; Lassnig et al ., 2021; Ramanathan and Samaranayake, 2021; Santos and Martinho, 2020; Veile et al ., 2019). Existing trends associate digital maturity with the scope and scale of implemented technologies (Tutak and Brodny, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have predominantly quantified Industry 4.0 development by measuring aspects such as strategy, organizational culture and technology (Kırmızı and Kocaoglu, 2022; Lassnig et al ., 2021; Ramanathan and Samaranayake, 2021; Santos and Martinho, 2020; Veile et al ., 2019). Existing trends associate digital maturity with the scope and scale of implemented technologies (Tutak and Brodny, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The results reveal that employee number has a significant impact on Industry 4.0. A possible explanation is that larger companies obtain correspondingly greater benefits from Industry 4.0 technologies (Masood and Sonntag, 2020), while small and medium-sized enterprises may struggle with digital transformation due to issues such as lack of material and human resources, capabilities, and strategies (Lassnig et al, 2022). This paper mainly focuses on large companies, but smaller companies might be differently affected in terms of their benefits from utilisation and implementation of Industry 4.0 technologies.…”
Section: Theoretical Contributions and Implicationsmentioning
confidence: 99%
“…Concerning the organization size, previous studies in industry sectors other than healthcare (e.g. Bosman et al, 2019;Sz asz et al, 2020;Lassnig et al, 2021) already suggested that larger firms may be more prone to an extensive adoption of I4.0 technologies. I4.0 usually requires a capital investment upfront to install the proper infrastructure to support the application of new technologies.…”
Section: Hypotheses Developmentmentioning
confidence: 99%